Ca2+-activated chloride channel activity during Ca2+ alternans in ventricular myocytes. Issue 6 (1st November 2016) - Kanaporis, Giedrius; Blatter, Lothar A.
ABSTRACT: Cardiac alternans, defined beat-to-beat alternations in contraction, action potential (AP) morphology or cytosolic Ca transient (CaT) amplitude, is a high risk indicator for cardiac arrhythmias. We investigated mechanisms of cardiac alternans in single rabbit ventricular myocytes. CaTs were monitored simultaneously with membrane currents or APs recorded with the patch clamp technique. A strong correlation between beat-to-beat alternations of AP morphology and CaT alternans was observed. During CaT alternans application of voltage clamp protocols in form of pre-recorded APs revealed a prominent Ca 2+ -dependent membrane current consisting of a large outward component coinciding with AP phases 1 and 2, followed by an inward current during AP repolarization. Approximately 85% of the initial outward current was blocked by Cl − channel blocker DIDS or lowering external Cl − concentration identifying it as a Ca 2+ -activated Cl − current (ICaCC ). The data suggest that ICaCC plays a critical role in shaping beat-to-beat alternations in AP morphology during alternans.